Therapy with young men : 16-24 year olds in treatment - Verhaagen, David Allan (Routledge series on counseling and psychotherapy with boys and men, 2010)
Young adult men in their late teens and early twenties are statistically the least happy of any group of males surveyed. What's more, scholarly research tells us that adolescent boys and young men have the highest rates of behavioral problems, completed suicides, and drug and alcohol problems of any demographic group. Young men frequently come into therapy with unresolved identity issues, behavioral problems, and drug and alcohol problems. They also tend to have greater problems managing their emotions and successfully negotiating close interpersonal relationships, which makes therapy more com.